Synthesis and Characterization of Some Ni(II) Mixed Ligand Complexes with Amino Acids - Kumar Kashap, Anil; Mohabey, Hemlata (Asian Journal of Chemistry, 2010)
Some Ni(II) complexes of the type [Ni (AB) (H2O)2] with bidentate amino acids like serin, threonine, α-amino butyric acid have been synthesised and characterized by elemental analysis, electronic, infrared spectra, magnetic moments. Differential thermal analysis data show that these complexes are thermally stable upto ∼ 350ºC and they decomposed to yield pure NiO at 700ºC. The value of magnetic moment shows that the complexes are paramagnetic with two unpaired electrons. The spectral studies suggest octahedral symmetry for these complexes.